Evidence of Dynamic Crustal Deformation in Tohoku, Japan, From Time‐Varying Receiver Functions. Issue 10 (5th October 2017) - Porritt, R. W.; Yoshioka, S.
Abstract: Temporal variation of crustal structure is key to our understanding of Earth processes on human timescales. Often, we expect that the most significant structural variations are caused by strong ground shaking associated with large earthquakes, and recent studies seem to confirm this. Here we test the possibility of using P receiver functions (PRF) to isolate structural variations over time. Synthetic receiver function tests indicate that structural variation could produce PRF changes on the same order of magnitude as random noise or contamination by local earthquakes. Nonetheless, we find significant variability in observed receiver functions over time at several stations located in northeastern Honshu. Immediately following the Tohoku‐oki earthquake, we observe high PRF variation clustering spatially, especially in two regions near the beginning and end of the rupture plane. Due to the depth sensitivity of PRF and the timescales over which this variability is observed, we infer this effect is primarily due to fluid migration in volcanic regions and shear stress/strength reorganization. While the noise levels in PRF are high for this type of analysis, by sampling small data sets, the computational cost is lower than other methods, such as ambient noise, thereby making PRF a useful tool for estimating temporal variations in crustal structure. Key Points: The strong shaking of the Tohoku‐oki earthquake‐induced fluid migration and stress reorganization in the Tohoku inland region Synthetic PRF tests indicate structural change can be mapped by variations in PRF Stations showing high anticorrelation after the Tohoku‐oki earthquake are well distributed throughout Tohoku